Multidisciplinary intervention of early, lethal metastatic prostate cancer: Report from the 2015 Coffey‐Holden Prostate Cancer Academy Meeting. Issue 2 (19th October 2015) - Miyahira, Andrea K.; Lang, Joshua M.; Den, Robert B.; Garraway, Isla P.; Lotan, Tamara L.; Ross, Ashley E.; Stoyanova, Tanya; Cho, Steve Y.; Simons, Jonathan W.; Pienta, Kenneth J.; Soule, Howard R.
Abstract : Background: The 2015 Coffey‐Holden Prostate Cancer Academy Meeting, themed: "Multidisciplinary Intervention of Early, Lethal Metastatic Prostate Cancer, " was held in La Jolla, California from June 25 to 28, 2015. Methods: The Prostate Cancer Foundation (PCF) sponsors an annual, invitation‐only, action‐tank‐structured meeting on a critical topic concerning lethal prostate cancer. The 2015 meeting was attended by 71 basic, translational, and clinical investigators who discussed the current state of the field, major unmet needs, and ideas for addressing earlier diagnosis and treatment of men with lethal prostate cancer for the purpose of extending lives and making progress toward a cure. Results: The questions addressed at the meeting included: cellular and molecular mechanisms of tumorigenesis, evaluating, and targeting the microenvironment in the primary tumor, advancing biomarkers for clinical integration, new molecular imaging technologies, clinical trials, and clinical trial design in localized high‐risk and oligometastatic settings, targeting the primary tumor in advanced disease, and instituting multi‐modal care of high risk and oligometastatic patients. Discussion: This article highlights the current status, greatest unmet needs, and anticipated field changes that were discussed at the meeting toward the goal of optimizing earlier interventions to potentiate cures in high‐risk and oligometastatic prostate cancer patients. Prostate 76:125–139, 2016 . © 2015 Wiley Periodicals, Inc.